The complete ARKit course build 11 augmented reality apps - Slim, Rayan; Percival, Rob (Packt Publishing, 2018)
"This course will take you on a journey where you'll learn to build 11 High-Level AR Apps using ARKit in iOS 11 and Swift 4. ARKit allows developers to create augmented reality apps for Apple's newly launched iOS 11. This new technology opens up the door for creative people and mobile app designers to build new experiences in a brand new industry that is expected to be worth USD165 billion by 2024!. This course will teach you to use textures to make cool 3D models, Display and animate 3D models in the camera view of the real world, Launch projectiles in the real world and lot more."--Resource description page
Title from resource description page (viewed December 3, 2018)
Keywords: iOS (Electronic resource); Augmented reality; Application software -- Development; IOS (Electronic resource); Réalité augmentée; Logiciels d'application; Développement; augmented reality; Application software; Development; Electronic videos